Correction: Glycosylated naphthalimides and naphthalimide Tröger's bases as fluorescent aggregation probes for Con A. Issue 8 (31st January 2019) - Calatrava-Pérez, Elena; Delente, Jason M.; Shanmugaraju, Sankarasekaran; Hawes, Chris S.; Williams, Clive D.; Gunnlaugsson, Thorfinnur; Scanlan, Eoin M.
Abstract : Correction for 'Glycosylated naphthalimides and naphthalimide Tröger's bases as fluorescent aggregation probes for Con A' by Elena Calatrava-Pérez et al., Org. Biomol. Chem., 2019, DOI: 10.1039/c8ob02980f.